The cultural code of the nation – crystallisation and enrichment of the past experience - Babosov, Evgenii M. (Journal of the Belarusian State University. Sociology, 2023)
The essence of the nation’s cultural code is clarified. The system of goals, objectives and tools for the implementation of traditional spiritual and moral values, which contributes to ensuring the national security of the country, is described. The main components of the cultural code of the Belarusian people are distinguished, which include traditional spiritual and moral values: life, human rights and freedoms, patriotism, citizenship, a strong family, creative work, priority of the spiritual over the material, humanism, mercy, justice, mutual assistance and mutual respect, continuity of generations. The article reveals the constructive significance of the Belarusian cultural code in the reproduction and development of the people’s historical memory experience, as well as in the creating a projection towards a better future for the Republic of Belarus.
Keywords: cultural code; historical memory; traditions; values